Modeling the prediction of the session rating of perceived exertion in soccer: Unraveling the puzzle of predictive indicators - Geurkink, Y.; Vandewiele, G.; Lievens, M.; de Turck, F.; Ongenae, F.; Matthys, S. P. J.; Boone, J.; Bourgois, J. G. (International Journal of Sports Physiology and Performance, 2019)
Soccer training consists of structurally and systematically performed general and specific exercises to improve physical abilities and acquire skills. The adaptations imposed by a training stimulus take place on an anatomical, physiological, biochemical, molecular, and functional level. The content of a training session is usually prescribed by the coach and can be defined as the external training load. The total external training load comprises all of the players` actions during a training session and is generally quantified using tracking technology. The external training load elicits an internal physiological stress, or the internal training load. However, the internal training load is not only dependent on the imposed external training load, but also on the players` individual characteristics (ICs).